Fabrication of N‐doped Graphene–Carbon Nanotube Hybrids from Prussian Blue for Lithium–Sulfur Batteries. Issue 8 (21st December 2016) - Su, Dawei; Cortie, Michael; Wang, Guoxiu
Abstract : Hybrid nanostructures containing 1D carbon nanotubes and 2D graphene sheets have many promising applications due to their unique physical and chemical properties. In this study, the authors find Prussian blue (dehydrated sodium ferrocyanide) can be converted to N‐doped graphene–carbon nanotube hybrid materials through a simple one‐step pyrolysis process. Through field emission scanning electron microscopy, transmission electron microscopy, X‐ray diffraction, Raman spectra, atomic force microscopy, and isothermal analyses, the authors identify that 2D graphene and 1D carbon nanotubes are bonded seamlessly during the growth stage. When used as the sulfur scaffold for lithium–sulfur batteries, it demonstrates outstanding electrochemical performance, including a high reversible capacity (1221 mA h g −1 at 0.2 C rate), excellent rate capability (458 and 220 mA h g −1 at 5 and 10 C rates, respectively), and excellent cycling stability (321 and 164 mA h g −1 at 5 and 10 C (1 C = 1673 mA g −1 ) after 1000 cycles). The enhancement of electrochemical performance can be attributed to the 3D architecture of the hybrid material, in which, additionally, the nitrogen doping generates defects and active sites for improved interfacial adsorption. Furthermore, the nitrogen doping enables the effective trapping of lithium polysulfides on electroactive sites within the cathode, leading to a much‐improved cycling performance. Therefore, the hybrid material functions as a redox shuttle to catenate and bind polysulfides, and convert them to insoluble lithium sulfide during reduction. The strategy reported in this paper could open a new avenue for low cost synthesis of N‐doped graphene–carbon nanotube hybrid materials for high performance lithium–sulfur batteries. Abstract : A Fe3 C@nitrogen‐doped graphene–carbon nanotube (Fe3 C@N‐GE–CNTs) hybrid material for sulfur storage in lithium–sulfur batteries is reported. The new hybrid material is prepared by a one‐step pyrolysis process using dehydrated sodium ferrocyanide as a precursor. Lithium–sulfur batteries made with these cathodes demonstrate outstanding electrochemical performances.